Catecholamine Use is Associated With Enterocyte Damage in Critically Ill Patients. Issue 5 (May 2015) - Piton, Gaël; Cypriani, Benoit; Regnard, Jacques; Patry, Cyrille; Puyraveau, Marc; Capellier, Gilles
Abstract : ABSTRACT: Small bowel damage is frequent but underdiagnosed among critically ill patients with shock. High catecholamine doses may have a deleterious effect on mesenteric blood flow. Plasma intestinal fatty acid–binding protein (I-FABP) concentration is a marker of enterocyte damage, whereas plasma citrulline concentration is a marker of functional enterocyte mass. We hypothesized that high doses of catecholamines in critically ill patients may be associated with enterocyte damage. This study aimed to determine the link between catecholamine use and dose with enterocyte damage. This is a prospective observational study performed in a large regional university teaching hospital. Critically ill patients requiring epinephrine and/or norepinephrine at admission to a medical intensive care unit (ICU) were included, as well as controls not receiving catecholamines. We evaluated at admission plasma I-FABP and citrulline concentrations, abdominal perfusion pressure (APP), and variables relating to prognosis and treatment. Patients were categorized according to the quartiles of catecholamine dose at ICU admission. Sixty critically ill patients receiving catecholamines and 27 not receiving catecholamines were included. Plasma I-FABP was higher among patients receiving catecholamine than in controls. Among patients receiving catecholamines, a dose of 0.48 γ kg −1 min −1 or more at ICU admission was associated with a higher I-FABP concentration. A Sepsis-related Organ Failure Assessment score higher than 11 and plasma I-FABP more than 524 pg mL −1 at ICU admission were independently associated with 28-day mortality (odds ratio, 4.0 [1.24–12.95] and odds ratio, 4.90 [1.44–16.6], respectively). Catecholamine use is associated with I-FABP elevation in critically ill patients. Critically ill patients receiving more than 0.48 γ kg −1 min −1 of epinephrine and/or norepinephrine at ICU admission have high I-FABP concentrations. This suggests that enterocyte damage reflects the severity of shock, and an adverse effect of catecholamines per se is possible.